Deceptive Foreign Credential Evaluation Services - Gollin, George (International Higher Education, 2013)
Foreign credential evaluation services play an increasingly important role in facilitating the movement of university students and graduates across national borders. But this unregulated sector of higher education is replete with unscrupulous agencies that provide deceptive evaluations for the customers of degree mills.